1980
DOI: 10.3109/17453678008990768
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotics and Bone Cements:Experimental and Clinical Long-Term Observations

Abstract: Comparing several antibiotics and different bone cements, the mixture of Palacok R (polymethylmethacrylate, PMMA) with gentamicin proved to be the most suitable one as far as a high and sustained release of the antibiotic from the artificial resin is concerned. A antinuous leaching of gentamicin was observed for more than 5 years. w t a m i c i n proved to be stable in Palacos R for the whole period of time. The release of 12 antibiotics from Palaas R was evaluated in witro. Four other bone cements were includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
114
0
3

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 256 publications
(121 citation statements)
references
References 9 publications
4
114
0
3
Order By: Relevance
“…We found that gentamicin release from both the prefabricated ALBC spacers and the hand-mixed ALBC was highest initially but then slowed after the first day. Our findings are consistent with previously reported release data from ALBC [12,23]. The amount of gentamicin that is released from the prefabricated ALBC spacer surfaces is more than we measured from 1 g/batch ALBC, but less than we measured from higher antimicrobial loads of 5 g or 10 g per batch of hand-mixed ALBC.…”
Section: Discussionsupporting
confidence: 92%
“…We found that gentamicin release from both the prefabricated ALBC spacers and the hand-mixed ALBC was highest initially but then slowed after the first day. Our findings are consistent with previously reported release data from ALBC [12,23]. The amount of gentamicin that is released from the prefabricated ALBC spacer surfaces is more than we measured from 1 g/batch ALBC, but less than we measured from higher antimicrobial loads of 5 g or 10 g per batch of hand-mixed ALBC.…”
Section: Discussionsupporting
confidence: 92%
“…With the exception of ticarcillin, antibiotic concentrations in the granulation tissue surrounding the beads exceeded 30 g/ml even 28 days after implantation. In pharmacokinetic studies in patients after implantation of gentamicin-impregnated PMMA, concentrations of up to 150 g/ml active gentamicin were observed in wound exudates derived directly from the vicinity of the implanted cement (49). Besides the nonbiodegradable PMMA, numerous biodegradable materials have been studied for use as local drug delivery systems for antibiotics (27).…”
mentioning
confidence: 99%
“…The first of the two [21] does not study or reference graft lengths, and the second [57] recommends VBGs for greater than 6-cm grafts based on an additional three articles [22,25,48]. A look at those three articles finds that one [25] also recommends VBGs for greater than 6-cm grafts and cites a case series of eight VBGs for tibial defects [13] and subsequently references numerous sources of low relevance [2,10,11,30,32,45,47,[51][52][53][54]. Another of the three articles [22] is a case series of 14 VBGs used for tibial defects, although only four grafts exceed 3 cm.…”
Section: Introductionmentioning
confidence: 99%